Pengembangan Potensi Destinasi Desa Wisata Menggunakan Indeks Pembangunan Desa Di Balesari Kecamatan Windusari Kabupaten Magelang - Bambang Kuncoro; Joko Tri Nugraha; Retno Dewi (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2019)
Enacted Law No. 6 of 2014 concerning Villages can be a solution to the problem of disparity between cities and villages. Balesari is one of the villages in Windusari District which has an area of 387 ha or about 3.34 percent of the area of Windusari District. The population of Balesari is 2,788 people. A total of 1,421 were male, while the remaining 1,367 were female. The objectives of this study are: (1) Analyzing the potential in Balesari Village based on the village development index variable and; (2) Prepare policy recommendations as an effort to realize Balesari tourism village and community welfare. The approach used is a case study with interactive model analysis techniques. Research location in Balesari Village. The technique of collecting data through interviews and observation. This research has a very important meaning because it has a contribution to the discovery of the root cause of the problem of not optimal development of rural areas in Indonesia. The results of the research in the field show the results: (1) Calculation of Balesari village potential using the VillageDevelopment Index of 48.72119 means that villages have availability and access to basic services, infrastructure, accessibility or transportation, public services and minimal government administration; (2) Local government policies in controlling tourism development in Balesari Village do not yet exist; (3) Community activities in zalacca gardening and raising livestock can be packaged as one of the tourist attractions.